Retreatment after primary spontaneous pneumothoraxes managed with primary tube thoracostomy or surgery - Vilkki, Valtteri A.; Kytö, Ville; Vilkki, Vesa; Gunn, Jarmo M. (Sage Publications Ltd., 2025)
Background and aims: There is a paucity of data on later healthcare visits and retreatments after primary treatment of spontaneous pneumothorax. The main purpose of this study was to describe retreatment rates up to 5 years after primary spontaneous pneumothorax treated with either surgery or tube thoracostomy (TT) at index hospitalization in Finland between 2005 and 2018 to estimate the burden of primary spontaneous pneumothorax on the healthcare system.
Methods: Retrospective registry-based study of patients with primary spontaneous pneumothorax treated with TT or surgery in Finland in 2005-2018. Rehospitalization and retreatment for recurrent pneumothorax and complications attributable to initial treatment were identified.
Results: The total study population was 1594 patients. At 5 years, 53.2% (384/722) of TT treated and 33.8% (295/872) of surgically treated patients had undergone any retreatment. Surgery was associated with a lower risk of recurrence than TT (hazard ratio (HR) 0.50, 95% confidence interval (CI) 0.43-0.56, p < 0.001). Male sex was associated with a lower risk of recurrent treatment (HR 0.75, 95% CI 0.63-0.90, p = 0.001). Higher age decreased the risk of recurrent treatment (HR 0.99, 95% CI 0.99-0.99, p < 0.001). At 5 years, 36.0% (260/722) of the TT treated and 18.8% (164/872) of the surgically treated had undergone reoperation at some point.
Conclusions: Reintervention rates and repeat hospital visits after TT and surgery were surprisingly high at long-term follow-up. Occurrences of retreatment and reoperation were significantly higher among primary spontaneous pneumothorax patients treated with TT at index hospitalization than among patients treated with surgery.